2019
DOI: 10.1002/dta.2703
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and optimization of SAR‐PAGE tests for erythropoietins in doping analysis

Abstract: Erythropoietins (EPOs) are substances listed in S2 of the World Anti‐Doping Agency (WADA) Prohibited List and are used commonly by athletes to increase endurance performance. According to the current WADA Technical Documents, sarcosyl‐polyacrylamide gel electrophoresis (SAR‐PAGE) followed by western blotting to differentiate erythropoietins based on their molecular weights is the only method that can be used for both screening and confirmation of all types of erythropoietins. The efficiency of immunopurificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…However, although CERA was detected in all 18 urine samples, the signal intensity of the band in different urine samples was observed to be erratic (Figure 4A). This phenomenon also occurred in our previous study when the StemCell® ELISA plate or the magnetic beads method were used for immunopurification of urine samples, and we assumed that the reason behind this might be the presence of proteins in urine samples, which might prevent the interaction between the antibody and CERA 11 …”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…However, although CERA was detected in all 18 urine samples, the signal intensity of the band in different urine samples was observed to be erratic (Figure 4A). This phenomenon also occurred in our previous study when the StemCell® ELISA plate or the magnetic beads method were used for immunopurification of urine samples, and we assumed that the reason behind this might be the presence of proteins in urine samples, which might prevent the interaction between the antibody and CERA 11 …”
Section: Resultssupporting
confidence: 60%
“…For the evaluation of the repeatability, all EPO and its analogs were spiked into blank urine or serum samples at amounts around their estimated LOD, except for CERA for urine samples. Based on previous research, 11 as the recovery of CERA in different urine samples was shown to be erratic, the amounts of spiked CERA for urine samples were much higher than its estimated LOD. Each blank urine sample was spiked with BRP (2.5 mIU), NESP (25 pg), EPO‐Fc (25 pg), and CERA (500 pg).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obtained analytical results were similar compared with other IA‐based sample preparation options, and the presented approach offered a rapid and simple alternative to other strategies based on, for example, magnetic nanoparticles or ELISA microplates. Zhou et al also elaborated on the critical role of the first IA‐based sample preparation step as well as the efficiency of the first blot for optimal analytical test results and recommended the use of ELISA microplates combined with a two‐step blotting protocol (1 hr at 1.0 mA/cm 2 plus 20 min at 1.56 mA/cm 2 ) instead of a commonly used single constant current approach for initial testing purposes, allowing for substantially reduced turnaround times for analytical test results 104 . For confirmatory analyses, IA‐assisted analyte extraction with antibody‐coated magnetic nanoparticles prior to gel electrophoresis and double blotting was advised.…”
Section: Peptide Hormones Growth Factors Related Substances and MImentioning
confidence: 99%